2018
DOI: 10.25046/aj030557
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Impact of Suicide on Active Witnesses: Predicting with Machine Learning

Abstract: Predicting the impact of suicide on incidental witnesses at an early stage helps to avert the possible side effect. When suicide is committed in public, incidental observers are left to grapple with it. In many cases, these incidental witnesses tend to experience the emotional side effect with time. In this study, we employed a Machine learning algorithms to predict the impact of suicide and suicidal attempt on incidental witnesses. This prediction was based on the accounts of suicide given by selected partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…While witnessed suicides are relatively rare in comparison to non-witnessed suicides, their impact on those who witness the death can be powerful and enduring [4][5][6]15,32]. In the current study, we developed criteria and a reliable coding scheme to classify suicides for being witnessed or not using information available in the law enforcement and medical/coroner narratives contained within the 2003-2017 NVDRS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While witnessed suicides are relatively rare in comparison to non-witnessed suicides, their impact on those who witness the death can be powerful and enduring [4][5][6]15,32]. In the current study, we developed criteria and a reliable coding scheme to classify suicides for being witnessed or not using information available in the law enforcement and medical/coroner narratives contained within the 2003-2017 NVDRS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of suicides occur in the decedent's home while alone and in private areas (e.g., bedrooms, closets, and bathrooms), increasingly a subset of suicides take place within view of others, such as using a firearm in the presence of other people, jumping in front of trains or subways, or leaping from bridges [3,4]. This has been referred to as witnessed suicide [5,6]. Studies have found that 4-10% of suicides are witnessed [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations